Konsep Belajar Mengajar Dalam Al-Qur’An: Telaah Implikasi Edukatif Qs. Al-‘Alaq (96): 1-5 - Muhammad Taufik (Universitas Islam Negeri Mataram, 2007)
The concept of teaching and learning in the al-Qur’an is basically able to, necessary, and must be exploited and developed continuously. This is to take into reality the superiority of the concepts from al-Qur’an and provide appropriate solution to the development of knowledge and science, education and teaching, and learning. In this perspective, as stated in Qs. al-‘Alaq (96):1-5, about the decree to learn nobly basically can be viewed as the model of learning which is in line with the model of learning recommended by latest findings of the researches in the field of sciences such as neuropsychology, neurobiology, and neuroscience where the subjects of learners are admitted and respected. Therefore, the command to read followed by the name of the Lord, the Almighty, and the direction or object of learning, contain problematical concepts started from intention and learning nobly and problem solving model which is also valued graciously.